Patterns of skeletal integration in birds reveal that adaptation of element shapes enables coordinated evolution between anatomical modules - Orkney, A; Bjarnason, A; Tronrud, BC; Benson, RBJ (Springer Nature, 2021)
Birds show tremendous ecological disparity in spite of strong biomechanical constraints imposed by flight. Modular skeletal evolution is generally accepted to have facilitated this, with distinct body regions showing semi-independent evolutionary trajectories. However, this hypothesis has received little scrutiny. We analyse evolutionary modularity and ecomorphology using three-dimensional data from across the entire skeleton in a phylogenetically broad sample of extant birds. We find strongly modular evolution of skeletal element sizes within body regions (head, trunk, forelimb and hindlimb). However, element shapes show substantially less modularity, have stronger relationships to ecology, and provide evidence that ecological adaptation involves coordinated evolution of elements across different body regions. This complicates the straightforward paradigm in which modular evolution facilitated the ecological diversification of birds. Our findings suggest the potential for undetected patterns of morphological evolution in even well-studied groups, and advance the understanding of the interface between evolutionary integration and ecomorphology.